Aphasia Compendium - Cătălin Jianu, Dragoș; Fior Mureșanu, Dafin (IntechOpen, 2022)
Aphasia is an acquired central disorder of language that impairs a person's ability to understand and/or produce spoken or writing language. The study of aphasia is important in different clinical and fundamental areas, including neurology, psychology, linguistics, and speech-language pathology. This book presents comprehensive information on the diagnosis and treatment of aphasias. Chapters cover such topics as linguistics and the study of aphasias, different types of aphasias, treatment approaches, imaging, and much more.